TUNGSTEN MINERALIZATION IN AREAS OF BASITE-ULTRABASITE MAGMATISM - Voyevodin V.N. (My University, 2004)
Most geologists share the concept of the lithophile origin of tungsten mineralization and its relation to granitoid magmatism. Nevertheless, geological-prospecting practice frequently reveals tungsten mineralization of the siderophile profile developed in areas of basite-ultrabasite magmatism. The siderophile Hg-Sb-W mineralization resulting from tectonomagmatic activation of young platforms is most well known. Its genesis is interpreted as telethermal with a presumably subcrustal mantle source of ore matter. In addition, there are many new data on the development of tungsten mineralization immediately in ultrabasites. The siderophile tungsten mineralization is highly variable, being represented by several genetic types: from true magmatic, carbonatite, autometasomatic, and rodingite (autoreaction skarns in ultrabasic massifs) to hydrothermal-metasomatic (telethermal). On the basis of geochemical data, two distribution types of tungsten mineralization are distinguished: basalt-related, when the content of the ore component decreases with increased acidity of igneous rocks, and granite-related, with successive W content growth in parallel with increased rock acidity. The basalt-related type of tungsten mineralization is characteristic of early geosynclinal differentiates of basaltic magma and postorogenic alkaline-basic-ultrabasic rocks, whereas the granitophile type is characteristic of orogenic rock complexes. In this connection, the basalt-related mineralization is confined only to early geosynclinal and postorogenic structures and the granite-related one, to orogenic structures. Additional research and geological prospecting works are needed to determine the potential of tungsten mineralization belonging to the basalt-related type.